Copurification of actin and desmin from chicken smooth muscle and their copolymerization in vitro to intermediate filaments (The Rockefeller University Press, 1979)
Desmin is a 50,000-mol wt protein that is enriched along with 100-A filaments in chicken gizzard that has been extracted with 1 M KI. Although 1 M KI removes most of the actin from gizzard, a small fraction of this protein remains persistently insoluble, along with desmin. The solubility properties of this actin are the same as for desmin: they are both insoluble in high salt concentrations, but are solubilized at low pH or by agents that dissociate hydrophobic bonds. Desmin may be purified by repeated cycles of solubilization by 1 M acetic acid and subsequent precipitation by neutralization to pH 4. During this process, a constant nonstoichiometric ratio of actin to desmin is attained. Gel filtration on Ultrogel AcA34 in the presence of 0.5% Sarkosyl NL-97 reveals nonmonomeric fractions of actin and desmin that comigrate through the column. Gel filtration on Bio-Gel P300 in the presence of 1 M acetic acid reveals that the majority of desmin is monomeric under these conditions. A small fraction of desmin and all of the actin elute with the excluded volume. When the acetic acid is removed from actin-desmin solutions by dialysis, a gel forms that is composed of filaments with diameters of 120-140 A. These filaments react uniformly with both anti-actin and anti-desmin antiserum. These results suggest that desmin is the major subunit of the muscle 100-A filaments and that it may form nonstoichiometric complexes with actin.